Vitamin D status in children with paralitic syndroms - Riga, Olena; Khaustov, Maxym; Mikhaylova, Aleksandra; Orlova, Natalia (My University, 2023)
The aim: Determination of serum 25(OH)D in the children with paralytic syndromes and its distribution depending on age, sex, taking anticonvulsant drugs, nutritional status for a period of one year (autumn-spring) of one center. Materials and methods: There were recruited of 77 children with paralytic syndromes and 73 health children for the same period aged from 1 till 18 years. The study included a scrutiny of medical history and analysis of medical documents, assessment of motor dysfunction by GMFCS, and nutritional status. Results: Among children with paralytic syndromes there were spastic tetraparesis 59.7%, malnutrition 92%, IV-V level of gross motor disfunction 80.5%, antiseizure medications 59.7% and cognitive impairment 77.9%. The variation of serum 25(OH)D is from 6.1 to 76.7 ng/mL with median 18.3 ng/mL in healthy children. The variation of serum 25(OH)D is from 2.2 to 83.0 ng/mL with median 14.8 ng/mL in children with paralytic syndromes (p=0.0103). Vitamin status among them is the following: insufficiency (21–29 ng/mL) – 28.7% vs 16.8%; deficiency (<20 ng/mL)–56.1 vs 72.2% (p=0.0300). The 25.9% children with paralytic syndromes and those who have deficiency demonstrate severe deficiency (<10 ng/mL) compare 10.9% in healthy children (p=0.00189). There is a tendency to decrease of serum 25(OH)D in children with paralytic syndrome older 7 years. Conclusions: We failed to record a significant difference in the 25(ОН)D between males and females, between different level of GMFCS, and anticonvulsants using. Deficiency of vitamin D in 2.25 times higher in children with paralytic syndromes and severe malnutrition. Additional researches with specific items are need in perspective.
Keywords: children; paralytic syndrome; vitamin D deficiency; COVID-19; 2023а